Weedy Hosts of the Diaprepes Root Weevil in Florida Sugarcane - Dennis C. Odero; Ronald Cherry (EDIS, 2021)
This publication provides an overview of Diaprepes root weevil and the role of weeds in providing harborage for the insect. Written by D. Calvin Odero and Ron Cherry, and published by the UF/IFAS Agronomy Department, July 2021.